2015
DOI: 10.1017/s0033291715002196
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and anxious-depression in Parkinson's disease over a 4-year period: a latent transition analysis

Abstract: BackgroundDepression and anxiety in Parkinson's disease are common and frequently co-morbid, with significant impact on health outcome. Nevertheless, management is complex and often suboptimal. The existence of clinical subtypes would support stratified approaches in both research and treatment.MethodFive hundred and thirteen patients with Parkinson's disease were assessed annually for up to 4 years. Latent transition analysis (LTA) was used to identify classes that may conform to clinically meaningful subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 55 publications
4
44
0
Order By: Relevance
“…Clinical studies have demonstrated the significance of adverse impact of even subclinical depression on quality of life. In the present study, the frequency of depression was found to be 27.6% [20][21][22] . Fluctuating course of depressive symptoms as in motor symptoms, especially more severely in off-periods, is of great significance for the optimization of treatment.…”
Section: Discussionsupporting
confidence: 51%
“…Clinical studies have demonstrated the significance of adverse impact of even subclinical depression on quality of life. In the present study, the frequency of depression was found to be 27.6% [20][21][22] . Fluctuating course of depressive symptoms as in motor symptoms, especially more severely in off-periods, is of great significance for the optimization of treatment.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, as has been suggested to optimize psychotherapy response for older adults, the current CBT protocol also was tailored to address the specific needs of the dPD population. For example, depressed PWP endorse very high levels of anhedonia, anxiety somatic symptoms, fatigue, sleep disturbance, rumination, and behavioral avoidance . They are also more psychiatrically complicated, with higher rates of comorbid anxiety and depression (vs matched controls), and depression chronicity .…”
Section: Discussionmentioning
confidence: 99%
“…As somatic dPD symptoms may worsen more with PD progression compared with other depressive symptoms, 37 dPD patients with significant somatic symptomatology may especially benefit from initiating combined treatment earlier in the PD process, to take advantage of the potential synergis- Moreover, as has been suggested to optimize psychotherapy response for older adults, 35 the current CBT protocol also was tailored to address the specific needs of the dPD population. For example, depressed PWP endorse very high levels of anhedonia, 38 anxiety 39,40 somatic symptoms, 41 fatigue, 42 sleep disturbance, 43 rumination, and behavioral avoidance. 44 They are also more psychiatrically complicated, with higher rates of comorbid anxiety and depression (vs matched controls), 39,40 and depression chronicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-motor complications are better predictors of disability, distress and rates to institutionalisation than the motor symptoms 3. Of the non-motor complications, mixed depression and anxiety is the most common psychiatric comorbidity, affecting ∼50% of PD patients, significantly more common that rates in the general population 4. Depression and anxiety are the strongest predictors of poorer quality of life,5 even in the advanced stages of the illness where the motor features have progressed fully 6.…”
Section: Introductionmentioning
confidence: 99%